Transrational Resonances Echoes to the Many Peaces (Springer International Publishing, 2018)
This book comprehensively gathers the current academic literature, field expertise and artistic developments on Wolfgang Dietrich's Many Peaces theory, in the ways it has been conceptualized and practiced by peace and conflict workers around the world. Both scholars and practitioners challenge and creatively explore the field of transrational peace philosophy, contributing their insights on elicitive methods and conflict mapping. The book is further enriched by artistic perspectives on integrative approaches to theatre for living and intercultural soundscapes. The articles collected here respond with innovative strength and vigor to the worldwide need for further research on peace and for practical approaches to conflict transformation. This book therefore equally appeals to scholars, peacebuilders and practitioners as well as artists engaged in conflict transformation. Josefina Echavarría Alvarez is Senior Lecturer at the Unit for Peace and Conflict Studies at the University of Innsbruck and invited international lecturer. Her research and peacebuilding work focus on migration and (in)security in Europe, as well as peace and reconciliation initiatives in Colombia. Daniela Ingruber is an Austrian war researcher and lecturer, journalist and editor, also working as a consultant for film productions and film festivals. Her main fields of research are conflict transformation through art, ethical journalism, war photography, storytelling as well as social hubs and their role in peaceful resistance. Norbert Koppensteiner is a Senior Lecturer at the Unit for Peace and Conflict Studies, University of Innsbruck, and program coordinator of the MA Program for Peace Studies at the same university. He is the author of the book 'The Art of the Transpersonal Self' and currently researches on transrational methods of peace research and on approaches to elicitive facilitation. .